P44 Oncological and reproductive outcomes after fertility-sparing surgery in women with cervical cancer: a systematic review and meta-analysis. (1st November 2019) - Tzafetas, M; Mitra, A; Lever, S; Kalliala, I; MacIntyre, D; Ghaem-Maghami, S; Kyrgiou, M
Abstract : Introduction/Background: Several approaches to fertility-sparing surgery in women with cervical cancer exist. Differences in radicality of parametrial excision are thought to exist according to surgical technique. Minimal access approaches may offer benefits in terms of enhanced patient recovery and nerve-sparing, however comparative oncological safety compared to an open approach is highly debated, especially in tumour volume >2cm. Pregnancy outcomes may also vary according to approach. This is the first systematic review and meta-analysis to compare the oncological and reproductive outcomes of simple or radical trachelectomy surgeries. Methodology: We searched relevant studies in MEDLINE, PUBMED and CENTRAL from inception to September 2018. Studies were eligible if they investigated oncological and/or reproductive outcomes following any radical trachelectomy surgical approach. Data were extracted in duplicate and additionally requested from authors where necessary. The primary outcome was cervical cancer recurrence rate after treatment. Secondary outcomes were margin involvement rate, residual tumour rate, conception rate and pregnancy outcomes (including 1st and 2nd trimester miscarriage rates, delivery rate, preterm labour rate (<37 weeks)). Random effects models were applied in STATA IC v15 to determine pooled estimates and corresponding heterogeneity. Sensitivity analyses were performed to analyse subgroups and where significant heterogeneity was detected. Results: We identified 59 eligible studies including over 2150 women. Recurrence rate varied by surgical approach: simple vaginal trachelectomy (SVT) 2% (95%CI 1–3%, I 2 =NA), vaginal radical trachelectomy (VRT) 3% (95%CI 2–4%, I 2 =0%) abdominal radical trachelectomy (ART) 1% (95%CI 0–2%, I 2 =35%), laparoscopic radical trachelectomy (LRT) 2% (95%CI 0–6%, I 2 =31%), radical robotic trachelectomy (RRT) 0% (95%CI 0–4%, I 2 =0%). Involved margins rate was lowest for LRT (7%, 95%CI 0–3%, I 2 =0%) and highest for RRT (7%, 95%CI 0–25%, I 2 =50.8%). Conception rate was highest for VRT (62%, 95%CI 47–75%, I 2 =84%) and lowest for ART (34%, 95%CI 25–44%, I 2 =55%). Conclusion: Balancing the oncological and fertility outcomes for fertility preservation techniques is challenging but achievable. Disclosure: Nothing to disclose.